The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/09585192.2017.1332673
|View full text |Cite|
|
Sign up to set email alerts
|

Working sick and out of sorts: a cross-cultural approach on presenteeism climate, organizational justice and work–family conflict

Abstract: A climate of presenteeism has important effects on employee well-being and the organization itself. Our study, based on surveys of health sector employees in six different countries (Brazil, Ecuador, Lebanon, Portugal, Russia and Spain) examines whether organizational justice plays a mediating role in the relationship between a presenteeism climate in the organization and work-family conflict (WFC). Our results indicate that the perception of organizational justice and the presenteeism climate do influence WFC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 72 publications
2
41
0
1
Order By: Relevance
“…This is vital in the highly competitive environments that characterize the healthcare sector, where employees with low autonomy and role ambiguity perceive a lack of social support and knowledge sharing [ 44 ]. With the introduction of the mediator role of presenteeism climate in the current study, we provide a contribution to the presenteeism literature by empirically reinforcing the importance of studying the policies of presence (and the pressure to be present) in the healthcare sector [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is vital in the highly competitive environments that characterize the healthcare sector, where employees with low autonomy and role ambiguity perceive a lack of social support and knowledge sharing [ 44 ]. With the introduction of the mediator role of presenteeism climate in the current study, we provide a contribution to the presenteeism literature by empirically reinforcing the importance of studying the policies of presence (and the pressure to be present) in the healthcare sector [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Taking into account that professionals in the Lebanese healthcare sector have to deal with an occasional lack of resources [ 32 ], we opted to include the job resource branch of the job demands-resource model in our study. In order to deal with political constraints, hospital managers are more prone to develop climates of presenteeism, where pressure to go to work despite being ill is very encouraged [ 14 ], [ 33 ]. As political and financial constraints are culturally prominent in Lebanon, we aim to evaluate the presenteeism culture among a sample of healthcare professionals.…”
Section: Introductionmentioning
confidence: 99%
“…In their research, Basic, Hanez, and Stringlhamber (2015), found that poor distributive and procedural justice negatively influences on work-family interference. Similarly, personnel of health department in six countries stated that the organizational justice has an impact on work-family conflict (Ferreira & Martinez, 2017).…”
Section: Effects Of Organizational Justice On Job Stress and Work-fammentioning
confidence: 99%
“…In 2016 the Brazilian population perceived the civil services quality as lower than the ideal considering the amount of taxes paid (CNI, 2016). Moreover, there was the challenge of improving civil service performance in a context of care-related, emotional works (pink collar), which are typically low-enriched as happens with some professional categories in the fields of education and health (Boyd, Hayward, Tuckey, Dollard, & Dormann, 2015;Ferreira et al, 2017;Koopmans et al, 2012;Parker, 2014). In addition, efforts to improve performance are understood as one-time and relatively standardized interactions (Ryan & Ployhart, 2013).…”
mentioning
confidence: 99%
“…On one hand, work enrichment does not prevent the occurrence of routine tasks required to the proper delivery of the service. On the other hand, as it is a work with strong emotional and relational component (Boyd et al, 2015;Buttigieg & West, 2013;Ferreira et al, 2017;Grandey, 2000;Kiss, De Meester, Kristensen, & Braeckman, 2014;Vilelas, 2013), changes on the objective and individual characteristics of the position and changes on the processes of social information and sense-making deserve attention.…”
mentioning
confidence: 99%